Sex-specific cardiovascular adaptations to simulated microgravity in Sprague-Dawley rats - Ebrahim Elsangeedy; Dina N. Yamaleyeva; Nicholas P. Edenhoffer; Allyson Deak; Anna Soloshenko; Jonathan Ray; Xuming Sun; Omar H. Shaltout; Nildris Cruz-Diaz; Brian Westwood; Daniel Kim-Shapiro; Debra I. Diz; et al. (npj Microgravity)
Abstract Men and women have different cardiovascular responses to spaceflight; however, few studies have focused on direct comparisons between sexes. We investigated the mechanisms of aortic stiffening in socially and sexually mature 20-week-old male and female Sprague Dawley (SD) rats exposed to hindlimb unloading (HLU) for 14 days. Pulse wave velocity (PWV) was greater in the aortic arch of females after HLU versus control females (n = 6–8). HLU had no effect on aortic PWV in males (n = 5–6). Aortic α smooth muscle actin, myosin, collagen, elastin, and collagen-to-elastin ratio were not different in rats of either sex following HLU. The levels of G protein-coupled estrogen receptor (GPER) were lower in the aorta of SD females exposed to HLU compared with female controls but were not altered in males. HLU females also had lower aortic PPARγ, increased oxidative stress markers, and diastolic dysfunction compared with control females. GPER agonist G1 prevented the increase in PWV and 8-hydroxy-2’-deoxyguanosine without altering PPARγ or p47phox in HLU females (n = 4 in each group) suggesting that lower GPER may contribute to arterial stiffening in the setting of simulated microgravity. This study highlights sex-specific vascular adaptations to the state of simulated microgravity.